Customer Satisfaction Analysis with Servqual and Kano Model Integration to Improve the Quality of Online Transportation Services - Insan Zaenul Muttaqin; Muhammad Ali Akbar; Bintang Nidia Kusuma (Global Writing Academica Researching and Publishing, 2026)
The growth of online transportation services has intensified competition among providers while generating various user complaints, making service quality evaluation increasingly important, particularly in developing regions such as Purwakarta Regency, where user characteristics differ from those in major cities. This study aims to analyze customer satisfaction and determine service improvement priorities for online transportation through the integration of the Service Quality (SERVQUAL) Gap 5 method and the Kano Model. A quantitative approach was employed using primary data from 100 respondents selected through purposive sampling. The instrument was a structured questionnaire measuring 15 service attributes across five SERVQUAL dimensions, and it was proven valid and reliable. The SERVQUAL analysis yielded an average perception score of 3.40 and an expectation score of 3.44, with a total gap of -0.05, indicating that service performance remains slightly below customer expectations. Of the 15 attributes, 8 showed negative gaps, with the largest found in pickup punctuality (-0.22), local route mastery (-0.19), and fare transparency (-0.14); at the dimensional level, the largest gap occurred in the Reliability dimension (-0.11). Integration with the Kano Model identified two Must-be attributes as the top improvement priorities, pickup punctuality and drivers’ mastery of local routes, while six other Indifferent attributes only need to be maintained and monitored. This study confirms that integrating SERVQUAL and the Kano Model can not only identify problematic attributes but also determine improvement priorities more strategically.